2008
DOI: 10.3762/bjoc.4.22
|View full text |Cite
|
Sign up to set email alerts
|

Perhalogenated pyrimidine scaffolds. Reactions of 5-chloro-2,4,6-trifluoropyrimidine with nitrogen centred nucleophiles

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…As described in our previous report, we synthesized a novel P-heteroarylated 1,3-diphosphacyclobutane-2,4-diyl via the S N Ar reaction of the 1,3-diphosphacyclobuten-4-yl anion. Reaction of phosphaalkyne 1 , , 0.5 equiv of t -butyllithium, and 5-chloro-2,4,6-trifluoropyrimidine afforded the pyrimidine-substituted 3 in 80% isolated yield via regioselective activation of the C–F bond by 2 (Scheme ). The calculated highest occupied molecular orbital (HOMO) of 2 , optimized at the CAM-B3LYP/6-31+G­(d) level (Figure ), indicated that P–C bond formation is not regulated by orbital control.…”
Section: Resultsmentioning
confidence: 99%
“…As described in our previous report, we synthesized a novel P-heteroarylated 1,3-diphosphacyclobutane-2,4-diyl via the S N Ar reaction of the 1,3-diphosphacyclobuten-4-yl anion. Reaction of phosphaalkyne 1 , , 0.5 equiv of t -butyllithium, and 5-chloro-2,4,6-trifluoropyrimidine afforded the pyrimidine-substituted 3 in 80% isolated yield via regioselective activation of the C–F bond by 2 (Scheme ). The calculated highest occupied molecular orbital (HOMO) of 2 , optimized at the CAM-B3LYP/6-31+G­(d) level (Figure ), indicated that P–C bond formation is not regulated by orbital control.…”
Section: Resultsmentioning
confidence: 99%
“…Large number of synthetic methods have been described for the preparation of pyrimidine-based compounds [11][12][13][14][15][16]. Cyclocondensation between guanidine, amidine or thiourea derivatives and 1,3-diketones or 1,3-diesters is the most classical method for the synthesis of the main pyrimidine core [15,17], whereas one of the approaches to prepare substituted pyrimidine rings is via halogenated pyrimidines [18][19][20], which are greatly commercially available. The most common reactions involving various halogenated pyrimidines are cross-coupling reactions since pyrimidine ring is an electron-deficient aromatic system being far more reactive in comparison with analogous benzene halides [17,20].…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic nucleophilic substitution in per-and poly-fluorinated arenes 1,2 is a valuable method for constructing highly functionalised heterocycles and aromatics. 3 Such compounds have been widely investigated by Chambers 4 and Sandford 5 and have been used as scaffolds for drug discovery. 6 The mechanistic and synthetic potential of fluorinated arenes has been reviewed.…”
mentioning
confidence: 99%